Projeto de circuito de bobina de Tesla com filtro de áudio FIR / Tesla coil circuit Project with FIR audio filter - Moura, Marcos Gabriel Lima (2022)
In this work, the small-signal model and the construction of a high-power transistor circuit similar to Tesla coils, called slayer exciter, are presented. In addition to the hardware design, this article also presents the design of an algorithm that uses an FIR (finite impulse response) filter to convert audio signals into PWM pulses, pulse width modulation, at the input of the circuit, which generate arcs. at the frequency of the input pulse, thus producing music.